Hilbert coefficients of ideals under perturbation of an ideal - Linh, Cao Huy; Tan, Ton That Quoc (Hue University Journal of Science: Natural Science, 2024)
Let (R, m) be a noetherian local ring, J an m-primary ideal of R and I = (f1, ..., fr) an ideal generated by a filter regular sequence f1, ..., fr of R. In this paper, we will prove the preserve of Hilbert coefficients of R/I with respect to J under J-adic perturbation of I, provided that J is a parameter ideal generated by a d-sequence of R/(f1, ..., fi) for i = 1, ..., r.